2010
DOI: 10.1093/europace/euq303
|View full text |Cite
|
Sign up to set email alerts
|

MEDAFI-Trial (Micro-embolization during ablation of atrial fibrillation): comparison of pulmonary vein isolation using cryoballoon technique vs. radiofrequency energy

Abstract: A considerable portion of patients with AF but without any neurological symptoms had chronic cerebral lesions before PVI. Additional acute lesions could be added after the procedure. Both ablation techniques showed additional cerebral acute lesions with no neurological symptoms after PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 35 publications
7
95
1
3
Order By: Relevance
“…Pre-existing lesions were predominantly found in the frontal and parietal lobes, as demonstrated in this sample patient. There were a median of 8 lesions per subject (interquartile range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. spontaneous; 45% were electrical).…”
Section: Procedural Parametersmentioning
confidence: 99%
“…Pre-existing lesions were predominantly found in the frontal and parietal lobes, as demonstrated in this sample patient. There were a median of 8 lesions per subject (interquartile range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. spontaneous; 45% were electrical).…”
Section: Procedural Parametersmentioning
confidence: 99%
“…Patients clinical characteristics such as age 18,19 , previous episodes of AF 20 ] were associated with the occurrence of SCI following transcatheter ablation.…”
Section: Cerebral Ischemia and Atrial Fibrillation Ablationmentioning
confidence: 99%
“…19,20 In addition to these clinically apparent ischemic strokes, brain imaging can identify further cerebral damage in patients after LACA (Table 2), similar to those reported after invasive cardiovascular procedures like diagnostic coronary angiography, carotid endarterectomy, or cardiac surgery. [21][22][23][24][25][26] Lickfett et al were the first to demonstrate the utility of diffusionweighted MRI to detect clinically "silent" strokes after LACA. A recent update of their observational cohort study indicated ischemic lesions in 11.3% patients, whereas physical examination revealed a transient reflex abnormality in 1 patient.…”
Section: Laca-associated Strokementioning
confidence: 99%
“…23 Smaller nonrandomized MRI studies reported acute brain lesions in 7.9% to 9.5% of all patients after LACA using radiofrequency or cryoenergy. 24,25 A nonrandomized multicenter study revealed a significantly higher rate of diffusion-weighted MRI lesions after LACA using a multi-electrode nonirrigated pulmonary vein ablation catheter compared to an irrigated-tip radiofrequency catheter or a cryoballoon, respectively (33.3%, 7.4%, or 4.3%). 26 These findings were confirmed by a nonrandomized single-center study demonstrating more diffusion-weighted MRI-detected brain lesions after LACA using a multi-electrode nonirrigated ablation catheter (new lesions in 38.9% of these patients) compared to an irrigated-tip radiofrequency catheter (8.3%) or a cryoballoon (5.6%).…”
Section: Laca-associated Strokementioning
confidence: 99%
See 1 more Smart Citation